Healthy Diets and Sustainable Development Goals - Chigumete, Tinatsei Gabriella; Rath, Seema; Bosman, Sean James; Srinivas, Sunitha Chandrasekhar (Indian Journal of Pharmacy Practice)
Populations throughout the world are facing immense challenges caused by a global rise in non-communicable diseases and ongoing economic crises. Non-communicable diseases impose a large financial burden on many populations, but there continues to be an underinvestment in factors that negatively affect health. One of the targets of the Sustainable Development Goal 3 is to reduce non-communicable diseases by one third. Evidence shows that diet-related non-communicable diseases are the leading cause of death and morbidity, and that their burden is likely to increase if urgent remedial actions are not initiated on a large scale. Successful implementation and execution of diet-related health promoting policies are required to promote sustainable human development. Control measures and improved understanding of the benefits of healthy diets, as well as changes in population attitudes and practices towards healthier diets are required to reduce the prevalence of diet-related noncommunicable diseases successfully. Programs that are currently implemented have not reduced the burden of diseases significantly due to narrow goals and their limited rates of implementation.
Keywords: Sustainable Development Goals; Non-communicable diseases; Diet; Health promotion; Low-andmiddle income countries